Estimating population viability of the northern Great Plains piping plover population considering updated population structure, climate change, and intensive management - Swift, Rose J.; Anteau, Michael J.; Ellis, Kristen S.; MacDonald, Garrett J.; Ring, Megan M.; Sherfy, Mark H.; Toy, Dustin L. (Frontiers in Bird Science, 2023)
One challenge in wildlife conservation is understanding how various threats and management actions may influence long-term population viability, particularly when there is considerable uncertainty regarding population structure and vital rates. Reassessment of current knowledge and population trends is necessary for listed species to improve management actions that benefit conservation. We present an updated population viability analysis for northern Great Plains piping plovers (Charadrius melodus circumcinctus) based on the latest scientific data on survival, fecundity, and connectivity. Further, we explore the consequences of potential management actions and the stochastic effects of global climate change on population viability through changes in survival and fecundity. Our results predict elevated risks of extinction after 50 years (0.088 – 0.373) compared to previous predictions (0.033) based on assumed conditions of low connectivity among four major breeding groups structured as a metapopulation. We explored eight scenarios based on empirically derived, higher connectivity rates and found that the northern Great Plains population never had a mean predicted population growth rate greater than one (0.946 – 0.996). Both scenarios that simulated a reduction in adult survival showed higher extinction probabilities (0.267 – 0.373), whereas scenarios that simulated an increase in fecundity exhibited lower extinction probabilities (0.088 – 0.103). These results indicate that viability of the northern Great Plains population of piping plovers could be improved with management actions that increase fecundity as long as adult survival is not simultaneously reduced. Lastly, breeding groups appeared to function less independently when connectivity rates were higher, as the breeding population was divided evenly among breeding groups. This indicates that the presumed metapopulation structure of our study system may need to be re-evaluated, and that empirically based estimates of connectivity are essential to assessing population viability of mobile species that exhibit a spatially structured distribution.